2015
DOI: 10.4103/0970-0218.149271
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming of emergency contraception pill in India: Challenges and opportunities

Abstract: Background:Emergency Contraception Pill (ECP) is an essential intervention to prevent unwanted pregnancies. However, its use has remained low due to various barriers including reservations among medical fraternity.Materials and Methods:This paper presents findings on barriers to ECP's easy access for potential users from (i) a cross-sectional survey of providers' attitudes, beliefs, and practices and interviews with key opinion leaders, (ii) three consultations organized by Population Council with policymakers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Less than one third of Indian women are aware of it and less than 1% have used it. 15 Present study showed a large number of women who thought EC was synonymous to first trimester medical abortion, in line with a study by Ghike et. al who found that 11.7% of women in Maharashtra thought MTP was a form of contraception.…”
Section: Discussionsupporting
confidence: 92%
“…Less than one third of Indian women are aware of it and less than 1% have used it. 15 Present study showed a large number of women who thought EC was synonymous to first trimester medical abortion, in line with a study by Ghike et. al who found that 11.7% of women in Maharashtra thought MTP was a form of contraception.…”
Section: Discussionsupporting
confidence: 92%
“…Some senior officials of the MoHFW believed that there is no need to train healthcare providers in ECP, as the leaflet provided with the pill is self-explanatory. 9 As per NFHS-4 report, knowledge of Emergency contraception was present in 38.5% of women and 44% of men, who were interviewed. The report also says that percentage of women who have ever used emergency contraceptive pills was just 0.4% and percentage of women who have used emergency contraceptive pills in the last 12 months was just 0.2%.…”
Section: Discussionmentioning
confidence: 98%
“…Less than one-third women are aware of ECP and less than one percent has ever used it. 9 When ECP was introduced, no sustained efforts were made to educate about ECP at any level of providersdoctors, ANMs, and ASHA. Some senior officials of the MoHFW believed that there is no need to train healthcare providers in ECP, as the leaflet provided with the pill is self-explanatory.…”
Section: Discussionmentioning
confidence: 99%
“…The government procures ECPs and provides it free of cost at its health centres as well as at the doorsteps in rural areas through the accredited social health activist (ASHA). 6,7 However, according to the annual health survey (2010-11), only 0.12 percent of the rural women had ever used ECP. 8 NFHS 4 shows that 33.6% percent of women in rural and 47.7% % in rural area were aware of ECP.…”
Section: Use Of Ecp In Indiamentioning
confidence: 99%